THE INFLUENCE OF RATIO ANALYSIS TO THE DIVIDEND PAYOUT RATIO AND ITS IMPACT ON THE VALUE OF THE COMPANY LISTED ON THE MALAYSIA STOCK EXCHANGE - Rudi Sanjaya (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2019)
ABSTRACTFundamental factor has powerful influences to the dividend policy that indicated by the Dividend Payout Ratio (DPR), because of it shows the companies financial performance. The aim of this research is to determine the influence of fundamental factor that are consisting of Earning Per Share (EPS), Current Ratio (CR), Debt to Equity Ratio (DER) to the Dividend Payout Ratio (DPR) and its impact on corporate value is proxyed by Price Earning Ratio (PER) the oil palm plantation.This research was conducted using secondary data that obtained from www.bursamalaysia.com period 2009-2016. The analysis method used is descriptive statistics method and panel data regression method. The sample of this research was extracted with purposive sampling. The 88 corporate annual reports was analyzed as sampels. Testing hypothesis research using model fixed effect with eviews app tool 9 version.This results indicate that growth EPS, CR, DER, DPR and firm value in oil palm plantation companies in Malaysia Exchanges from 2009-2016 period on average fluctuate every year. Partially variable Earning Per Share (EPS) doesn’t have a significant effect on the variable Dividend Payout Ratio (DPR). Partially the variable Current Ratio (CR) has a significant effect on the variable Dividend Payout Ratio (DPR). Partially variable Debt to Equity Ratio (DER) doesn’t have significant effect on the variable Dividend Payout Ratio (DPR). Simultaneously and together the variable Earning Per Share (EPS), Current Ratio (CR), and Debt to Equity Ratio (DER) have a significant on the variable Dividend Payout Ratio (DPR). Partially variable Dividend Payout Ratio (DPR) has no significant effect on firm value variable (proxy with (PER) Price Earning Ratio).